Female Penghulu: Opportunities and Problems Within Indonesia's Civil Law System - Abdul Hakim; Tutik Hamidah; Ali Hamdan (International Journal of Sociology and Law, 2026)
This research is based on the shortage of functional penghulu officers, which has become a serious issue for the government, particularly the Ministry of Religious Affairs of Indonesia. This condition can affect the quality of services in marriage registration, family guidance, and the provision of legal certainty to the community. To overcome the emergency of penghulu personnel, it is necessary to propose that the position of penghulu also be granted equal access to women, whereas until now the position of penghulu has been dominated only by men. Therefore, this research aims to conduct a comprehensive study on the provisions regarding the opportunities and problems of female penghulu within Indonesia’s civil law system, in which civil law is the official positive legal umbrella governing penghulu affairs. This research is normative legal research employing a statutory approach and a conceptual approach. Meanwhile, the primary legal materials of this research consist of various laws and regulations directly related to penghulu affairs. The results of this research indicate that the opportunities for female penghulu within the civil law system are very open, constitutionally valid, and not subject to any normative prohibition. The problems arise when female penghulu are requested to act as guardians appointed by the court (wali hakim) or entrusted with the delegated guardianship of marriage (taukil wali). This is because, under Indonesia’s civil law, a wali hakim or a person receiving taukil wali is required to be male. In addition, another problem is the existence of a specific requirement to be male that must be fulfilled in the recruitment of penghulu personnel as stated in the Announcement Letter on the Recruitment of Candidates for Civil Servants of the Ministry of Religious Affairs.